2008
DOI: 10.1111/j.1540-5907.2007.00303.x
|View full text |Cite
|
Sign up to set email alerts
|

The Conditional Effect of Specialized Governance on Public Policy

Abstract: What are the policy consequences of creating functionally specialized venues for decision making? This study directly compares special districts with general purpose local governments to evaluate how specialization influences responsiveness and policy choice. Previous theorizing has assumed that specialization should have the same effect across all policy contexts. The findings presented here show instead that its effect is conditional on the status of public problems. Objective conditions related to a policy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
108
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(113 citation statements)
references
References 32 publications
5
108
0
Order By: Relevance
“…Some governmental structures typically considered “responsive” (e.g., ward‐based elections) are more likely to adopt landscape audits and less likely to adopt conservation rates. Yet the impact of some political institutions—the special‐district form in particular—on conservation policies apparently is contingent on climatic conditions, a finding consistent with past research (Mullin, 2007). Curiously, the council–manager charter form has a positive effect on the likelihood of both landscape audits and conservation.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Some governmental structures typically considered “responsive” (e.g., ward‐based elections) are more likely to adopt landscape audits and less likely to adopt conservation rates. Yet the impact of some political institutions—the special‐district form in particular—on conservation policies apparently is contingent on climatic conditions, a finding consistent with past research (Mullin, 2007). Curiously, the council–manager charter form has a positive effect on the likelihood of both landscape audits and conservation.…”
Section: Discussionsupporting
confidence: 85%
“…Controls for environmental conditions. Climatic conditions, customer demand patterns and supply sources are likely to drive conservation policies, and so a valid analysis of political institutions must account for these factors (Mullin, 2007; Hewitt, 2000). The current analysis uses three metrics to control for the effect of these environmental conditions.…”
Section: Empirical Analysismentioning
confidence: 99%
“…Regions with faster population growth should be more likely to adopt conservation rate structures in order to avoid costly plant and distribution system expansions and to forecast future demand more accurately (Beecher, 2010a;Chesnutt & Beecher, 1998). Mullin (2008) demonstrated that utilities with higher ratios of residential customers were more likely to adopt conservation rate structures. Because population growth and the ratio of residential customers are likely correlated, population growth is hypothesized to be the more important variable.…”
Section: Methodology Selectivity Parametersmentioning
confidence: 99%
“…Experiencing or perceiving environmental hazards can increase the political salience of that hazard as a policy issue (Mullin 2008). Moser and Ekstrom (2010) identified that perception of climate change hazard is the first stage for understanding climate adaptation issues.…”
Section: The Role Of Perceived Climate Change Hazardsmentioning
confidence: 99%
“…Cities can adapt to changes in the intensity and timing of major storm events by improving flood defenses and diversifying water supplies, including capturing storm water (Daigger 2009;Muller 2007). Finally, as climate change brings new distributions and timing of disease outbreaks and vectors (Patz et al 2005), cities can take steps to respond to these shifts through education campaigns and investments in medical services. Adaptation actions can be introduced as part of existing programs, or "mainstreamed" (UNDP/UNEP 2011), or as new, independent initiatives.…”
Section: The Scope Of Urban Adaptation Agendasmentioning
confidence: 99%